CULTURAL ADJUSTMENT PROBLEMS IN ACADEMIC LIFE EXPERIENCED BY INDONESIAN POSTGRADUATE STUDENTS IN LONDON - Erizal Lugman (Eltin Journal : Journal of English Language Teaching in Indonesia, 2022)
The number of Indonesian students studying in the United Kingdom is steadily rising. In previous studies, it has been shown that adjusting to a new culture is an essential factor in the academic success of international students. This research examines the academic challenges faced by Indonesian postgraduate students because of the significant cultural disparities between Western and Indonesian civilisations. Semi-structured interviews were conducted in this study to get information on students' issues about their academic. Using academic English in academic contexts was found to be the most challenging aspect for participants, along with students' inability to think critically. Nine out of eleven students said they struggled to write essays throughout the cultural transition period. Students' awareness of cultural differences between Indonesian and Western cultures, both in the classroom and outside of it, is suggested by the data.